How Do Mobile Social Apps Matter for College Students’ Satisfaction in Group-Based Learning? The Mediation of Collaborative Learning - Wang, Xuyan; Zhang, Renyu; Wang, Xiaojiong; Xu, Dongming; Tian, Fangqing (Frontiers in psychology, 2022)
Recently, many universities apply mobile tools to teaching practices. For instance, some teachers may set up groups on mobile social apps and assign course tasks and advise college students to submit papers online. Nevertheless, how these mobile social apps affect teaching practices, especially the process of students’ satisfaction needs to be further explored. To fill this research gap, we build a theoretical model of how mobile social apps’ functions affect course satisfaction from the perspective of Media Richness theory and the Uses and Gratifications (U and G) theory. A total of 186 valid questionnaires from college students in China were collected, and a structural equation model was built to test our research model. The results show that as: (1) only the communication function has positive impacts on knowledge sharing, while the impact of the information storing function and information distribution function on knowledge sharing is not significant; (2) knowledge sharing does not affect course satisfaction in a direct way, but it can act indirectly through promoting collaborative learning, which shows the mediating role of collaborative learning. The theoretical implications and practical implications of the study are discussed.